ANALISA PENGARUH FASHION BATIK GONG-GONG DI KOTA BATAM TERHADAP E-WOM DENGAN MEDIASI CUSTOMER SATISFACTION - Agnes Kristy; Fitriana Aidnilla Sinambela (Universitas Islam Negeri Alauddin Makassar, 2022)
Among the richness of Indonesian culture, Batik is a work of Indonesian cultural art admired by the world. Batik is an ancient art form of one of the best quality criteria. The meaning of Batik comes from the Old Javanese language, namely